A Call for Repairing the Harms of Colonization: Maine’s Bicentennial as an Opportunity for Truth, Acknowledgment, Resistance, and Healing - Arthur, Erika; Burns, Penthea (Maine Policy Review, 2020)
The authors examine the colonized history and present of Maine to recognize that the state’s bicentennial may not mean the same thing to all who live here. They explore the impact of settler colonialism on Wabanaki people and settler descendants and recognize the ways colonization lives in our laws, structures, policies, and worldview. And yet, in Maine today, there are already examples of the holistic, indigenous-led engagement, healing, and advocacy that this history and present call for, such as the work of Maine-Wabanaki REACH. However, this moment asks for many more of us who trace our lineages to settlers to commit to these processes. Using interviews, case studies, and literature reviews, this article proposes a set of questions that researchers, policymakers, advocates, and others can ask ourselves about our roles in processes of decolonization.
Keywords: Maine-Wabanaki REACH; decolonization; Maine Indian Claims Settlement Act